The Convention on the Elimination of All Forms of Discrimination against Women(CEDAW): with reference to violence against women and trafficking in women - Abdul Hak, Nora (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) is the international human rights treaty that is exclusively devoted to gender equality. It was adopted by the United Nations General Assembly on 18 September 1979 and entered into force on 3 September 1981. It is one of the most widely accepted human rights treaties and is often described as an international bill of rights for women. Article 2 States parties condemn discrimination against women in all its forms and agree to pursue by all appropriate means and without delay a policy of eliminating discrimination against women. The Convention requires that all States Parties reports to include statistical data on firstly, the incidence of violence against women, secondly, information on legislative and other measures taken to protect women against violence and finally, information on the provision of services for victims. Thus, the paper deliberates the relevant articles of the Convention which are included with the aim to protect the rights of women. Special focus of the discussion is on the issues of violence against women and women trafficking in Malaysia. These issues require special attention as to gauge the extent of compliance to CEDAW by the Malaysian government in combating these unresolved problems. Legal effects of reservations to CEDAW and the enforcement mechanisms will also be deliberated.